MY STORY - Rizki Ramadhan; Syeilendra Syeilendra; Yos Sudarman (SENDRATASIK UNP, 2017)
The purpose of this work was to narrate the author's life story by using a violin as the instrument. It told about the author's love of this cord instrument. Through the work of "My Story" the author expressed various kinds of feelings such as sadness, happiness, joy, anger, and disappointment through music composition. This work was played by 4 music players (quartet) with classical music style. They consisted of one violinist, one viola player, one flutist and one classical guitarist. The music composition in this work used the form of rondo composition. This composition emphasized circular circles of repetitions of sentences in the song. The first theme was played; after that, the second theme was introduced and developed. Before the third theme came up, the composition reverted to the first theme and it ended in the first theme after going through an unexpected third theme. Keywords : classical music, quartet, my story.